2020
DOI: 10.1371/journal.pone.0244086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sediment and stream transport on detecting a source of environmental DNA

Abstract: Environmental DNA (eDNA) can be used for early detection, population estimations, and assessment of potential spread of invasive species, but questions remain about factors that influence eDNA detection results. Efforts are being made to understand how physical, chemical, and biological factors—settling, resuspension, dispersion, eDNA stability/decay—influence eDNA estimations and potentially population abundance. In a series of field and controlled mesocosm experiments, we examined the detection and accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…by increasing the value of S p ) (Curtis et al, 2020; Jane et al, 2015; Pont et al, 2018). Additionally, eDNA can accumulate in benthic sediment, particularly when decay rates in sediment are slower than in the water column (Barnes et al, 2014; Nevers et al, 2020; Turner et al, 2015). Increased turbulence could resuspend FPOM (including eDNA) during extreme discharge events, obscuring the relationship between organism abundance and eDNA (Jane et al, 2015; Shogren et al, 2017).…”
Section: Integrating Environmental Dynamics Of Edna In Natural Ecosys...mentioning
confidence: 99%
“…by increasing the value of S p ) (Curtis et al, 2020; Jane et al, 2015; Pont et al, 2018). Additionally, eDNA can accumulate in benthic sediment, particularly when decay rates in sediment are slower than in the water column (Barnes et al, 2014; Nevers et al, 2020; Turner et al, 2015). Increased turbulence could resuspend FPOM (including eDNA) during extreme discharge events, obscuring the relationship between organism abundance and eDNA (Jane et al, 2015; Shogren et al, 2017).…”
Section: Integrating Environmental Dynamics Of Edna In Natural Ecosys...mentioning
confidence: 99%
“…In recent years, a new technique for investigating fish distribution in water, environmental DNA method, has been developed. Environmental DNA (eDNA) is DNA that creatures shed into their living environment, including water, sediment, soil, and even air [ 1 4 ]. Surveys using eDNA have been performed in rivers, lakes, and coastal areas [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that eDNA can be detected in standing water days after the source of the DNA has been removed, see, for example, Barnes et al ( 2014 ), but in running water samples of several liters has often been necessary to compensate for the reduced probability of detection caused by removal of eDNA by water flow (Rees et al, 2014 ). Field experiments in rivers with low discharge (<100 liters/second) has shown that eDNA concentrations are relatively stable the first 24 h after the source of DNA has been removed, but that eDNA concentration decreases with increased discharge (Jane et al, 2015 ; Nevers et al, 2020 ). The discharge when we collected the sample was much higher, and this should have reduced the probability of detection even more.…”
Section: Discussionmentioning
confidence: 99%